KEWAJIBAN BANK SEBAGAI ACQUIRER TERHADAP PEMBERLAKUAN PEMBEBANAN BIAYA TAMBAHAN (SURCHARGE) OLEH MERCHANT PADA TRANSAKSI KARTU KREDIT: Bank’s Obligations as an Acquirer Regarding the Imposition of Surcharges by Merchants on Credit Card Transaction - Farah Airitsa Hermawan; Siti Nurbaiti (Reformasi Hukum Trisakti, 2025)
Merchant Discount Rate is a fee charged by the Bank to merchants for transactions made using credit cards through Electronic Data Capture machines, the fee is prohibited to be charged to customers when making transactions, but in practice there are still many merchants who charge the fee to customers, especially when making payment transactions using credit cards. The problem formulation in this article is how the Bank's obligation as an acquirer towards the application of surcharge by merchants in credit card transactions. This research uses descriptive normative research method, with secondary data and primary data as support which is analyzed qualitatively with deductive inference. Results and conclusions of the study is illustrate that the application of additional fees is prohibited by Bank Indonesia Regulation Number 11/11/PBI/2009 concerning the Implementation of APMK Card Activities jo. Bank Indonesia Regulation Number 23/6/PBI/2021 concerning Payment Service Providers, but in its implementation this regulation still cannot be implemented properly due to the gap between regulations and what happens in the field, where the Bank has not been able to fully carry out its obligations in accordance with applicable regulations due to Bank business reasons.